Assessing the risk of corrosion in amine-based CO2 capture process. (September 2016) - Krzemień, Alicja; Więckol-Ryk, Angelika; Smoliński, Adam; Koteras, Aleksandra; Więcław-Solny, Lucyna
Abstract: This paper presents a study on the risk of corrosion within a post-combustion and amine-based carbon capture installation with the use of selected risk assessment methods like the HAZard and OPerability study (HAZOP), Delphi technique and Fault Tree Analysis (FTA). As in alkanolamine plants, due to economic reasons most of the equipment and piping is constructed of carbon steel, these parts of the installations may suffer from corrosion by several agents like wet acid gases, oxygen and products of the degradation of amines. The study presented within this paper shows this does not only occur in the case of carbon steel, but also other types of materials used within the installation may suffer from corrosion. The correct choice of materials is vital in ensuring the long-term performance, safety and operational availability of CO2 capture plants. A lack of information about previous operational problems or accidents within one-to-one size installations presents a great challenge when conducting risk assessment. This is why a methodology of risk identification and evaluation for CO2 capture installations is proposed, along with its practical application. This method is based on the experience gained from worldwide pilot plants and from a Polish research project on the CO2 capture process. All new technologies need to be investigated with special care, especially when having little knowledge about their behaviour while connected to the existing equipment of any power plant. Highlights: A study on the risk of corrosion within a post-combustion and amine-based carbon capture installation is presented. A methodology of risk identification and evaluation for CO2 capture installations was proposed. A combination of HAZOP study, Delphi technique and Fault Tree Analysis was applied in order to calculate the risk. The highest level of risk was identified in the area of rich amine solution and pipelines with wet acid gases. The most frequent reason for corrosion and amine degradation is the presence of heavy metals in amine solution.